CHOICE OF SURGICAL TREATMENT METHOD FOR PILONIDAL ABSCESS IN PREGNANT PATIENTS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background. Acute suppurative processes of the sacrococcygeal region in pregnant patients present a challenging clinical dilemma due to the critical need to balance surgical radicality with the minimization of fetal risks.Objective. To evaluate the efficacy and safety of various surgical approaches for pilonidal abscess (PA) management in pregnant patients across different trimesters of gestation.Materials and Methods. A retrospective analysis of 42 pregnant patients treated for PA was conducted. Patients were divided into two groups: Group I ($n=22$) underwent radical excision of the abscess along with adjacent soft tissues; Group II ($n=20$) underwent a two-stage approach (minimally invasive incision, drainage, and delayed radical surgery in the postpartum period).Results. In Group I, the wound complication rate was 13.6%, with a mean hospital stay of $9,2 ± 1,4$ days. In Group II, no wound complications were recorded during the gestational period, and the mean hospital stay was $4,1 ± 0,8$ days. Uterine hypertonus was observed in 18.1% of cases in Group I versus 5.0% in Group II; the threat of preterm labor occurred in 13.6% and 5.0% of cases, respectively.
Keywords: Pilonidal sinus, abscess, pregnancy, minimally invasive surgery, obstetric complications.